Hierarchy of values between religious high school students and secular ones in Lima - García Anchorena, Raiza (2016)
The purpose of this research was to compare the hierarchy of values among high school students, according to type of school (religious and secular) and sex. The sample was composed by 250 high school students (60.4% male, 52% religious school). The ages are in the range of 14 to 17 years (M = 15.47, SD = 0.63). The instrument used was the Portrait Value Questionnaire by Schwartz (2001), whose analysis of structure and internal consistency was satisfactory. To compare the hierarchy of values between the groups, top down correlations (rtd >) were used. According to the results, greater association (similarity) was found between the hierarchy of values depending on the type of school (rtd = .82) and, to a lesser degree by sex (rtd = .69). The comparative results show greater Benevolence, Self-Direction, Stimulation among women and Achievement among men. The implications of the comparative results are discussed.